Making the case for One Health - Hung Nguyen-Viet (International Livestock Research Institute, 2021)
Hung-Nguyen, co-leader of the Animal and Human Health Program at ILRI, describes the One Health approach and its benefits and explains why governments, investors and policymakers need to invest in the approach. This film is part of the ILRI and CGIAR 'Investing in One Health' video series.